Golden Bear Aide Dies - Vallejo Times-Herald (Vallejo Times-Herald)
Charles H. Pritchett, 56, of 1035 Castlewood Dr., died of an apparent heart attack Saturday night in Honolulu, Hawaii, while on the annual training cruise of the Golden Bear, California Maritime Academy ship. Mr. Pritchett, a retired Navy lieutenant, had been a medical technician at the academy the past 11 years. He had resided in Vallejo 15 years.